Powder Mixed Micro Electro Discharge Milling of Titanium Alloy: Analysis of Surface Roughness - Ali, Mohammad Yeakub; Adesta, Erry Yulian Triblas; Abdul Rahman, Nur Atiqah; Mohamad Aris, Erniyati (2011)
This paper presents effects of silicon carbide SiC powder concentration on micro EDM parameters on average surface roughness (Ra). The aim is to achieve minimum Ra value on titanium alloy (Ti-6Al-4V) machined with tungsten electrode for various level of concentration of SiC powder and discharge energy (E). By using two-parameter and four-level factorial design of experiment sixteen experiments were conducted. The measured surface roughness values were analyzed with input parameters using by Design Expert software. The minimum Ra value obtained was 0.75 μm for 16.8 g/L SiC powder concentration and 57.8 μJ energy discharge. The analysis of variance revealed that powder concentration is the most influential parameter.